Analysis of the Influence of Work Discipline, Work Environment, Leadership and Job Satisfaction on Performance - Lingga Ramadhana Arfi; Suryatunnisak, Suryatunnisak; Handoyo, Leonardus Teguh (Journal of Engineering Science and Technology Management, 2025)
This study is a quantitative study that aims to determine the effect of work discipline, work environment, leadership and job satisfaction on performance. The population used in this study was all 50 employees of Toptel Hotel Pekanbaru. The research sample was determined using a census sampling technique, which involves taking the entire population as the sample. Therefore, the sample size in this study was 50 employees. The data analysis technique used was quantitative analysis using multiple linear regression with the help of the Statistical Package for the Social Sciences (SPSS) program. The results of the study are as follows: 1) Work discipline has a positive and significant effect on performance. 2) The work environment has a positive and significant effect on performance. 3) Leadership has a positive and significant effect on performance. 4) Job satisfaction has a positive and significant effect on performance. 5) Together or simultaneously, work discipline, work environment, leadership, and job satisfaction have a positive and significant effect on performance.